Development and assessment of total thrombus-formation analysis system-based bleeding risk model in patients undergoing percutaneous coronary intervention. (15th February 2021) - Nakanishi, Nobuhiro; Kaikita, Koichi; Ishii, Masanobu; Kuyama, Naoto; Tabata, Noriaki; Ito, Miwa; Yamanaga, Kenshi; Fujisue, Koichiro; Hoshiyama, Tadashi; Kanazawa, Hisanori; Hanatani, Shinsuke; Sueta, Daisuke; et al.
Abstract: Background: Antithrombotic therapy is established for the treatment of various cardiovascular events. However, it has been shown to increase the bleeding risk. Total Thrombus-formation Analysis System (T-TAS) is reported to be useful for evaluating thrombogenicity. Here, we estimated whether T-TAS is useful for predicting bleeding events risk in patients undergoing percutaneous coronary intervention (PCI). Methods: This was a retrospective, observational study at Kumamoto University Hospital between April 2017 and March 2019. Blood samples obtained on the day of PCI were used in T-TAS to compute the thrombus formation area under the curve (AUC) (AR10 -AUC30, AUC for AR chip). We divided the study population into 2 groups according to the Academic Research Consortium for High Bleeding Risk (ARC-HBR) (182 patients in ARC-HBR positive, 118 in ARC-HBR negative). The primary endpoint was 1-year bleeding events that were defined by Bleeding Academic Research Consortium type2, 3, or 5. Results: The AR10 -AUC30 levels were significantly lower in the ARC-HBR positive group than in the ARC-HBR negative group (median [interquartile range] 1571.4 [1277.0–1745.3] vs. 1726.2 [1567.7–1799.6], p  < 0.001). The combination of ARC-HBR and AR10 -AUC30 could discriminate the bleeding risk, and improved predictive capacity compared with ARC-HBR by c-statistics. Decision-curve analysis also revealed that combining AR10 -AUC30 with ARC-HBR ameliorated bleeding risk-prediction. In multivariate Cox hazards analyses, combining ARC-HBR with lower AR10 -AUC30 levels was significantly associated with 1-year bleeding events. Conclusions: The results highlight that AR10 -AUC30 evaluated by T-TAS could be a potentially useful marker for predicting high bleeding risk in patients undergoing PCI. Highlights: Total Thrombus-formation Analysis System (T-TAS) is known to be useful for evaluating thrombogenicity. .The combination of ARC-HBR and AR10 -AUC30 levels determined by T-TAS could discriminate the bleeding risk, and improved predictive capacity. The AR10 -AUC30 could be a potentially useful marker for predicting high bleeding risk in patients undergoing PCI.